Comparative analysis of the functional aspects of mosque among different regions - Abd Talib, Rufaidah; Utaberta, Nangkula; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah; Ismail, Sumarni; Mohd Ariffin, Noor Fazamimah (American-Eurasian Network for Scientific Information, 2015)
Mosque is an important element of Islamic culture. Material in the Qur‟an and Hadith have generally been interpreted to show the meaning and usage of the mosque. Qur‟an and Hadith are main references and believing them are one of faith have to be hold by Muslims. If the function of the mosque has been justified in the Qur‟an and Hadith, why the liveliness and the function of the mosque are differ in every country. This paper focused on the early tradition, roots and culture that give huge impact on the liveliness of the mosque. These original tradition of one place shapes the social aspects and lifestyle, thus effected and altered the usage of mosque. Study begins with research on the Arab culture where Islam is originated. Then following with research on different country where Islam is spread around, focusing on America, China from the Orient following with Malaysia from East. Each country will be study on their brief original roots, the history of early Islam influence and relates to nowadays use of the mosque. The paper expect to show the pattern on how these old roots gives impact to the usage of the mosque, thus list out some of ways that function of the mosque can be used to the fullest.